Democratic Citizenship in Mathematics Teacher Preparation in South African Universities: Contradictions in Theory and Practice - Babawande Emmanuel Olawale (International Journal of Pedagogy and Teacher Education, 2022)
For individuals to become democratic citizens, they need to be exposed to at least three interrelated elements: collective identity, the privileges of membership, and social rights and benefits. This study investigates how South African universities prepare mathematics teachers for democratic citizenship. Data were generated from six mathematics teacher educators and 75 second- to fourth-year student teachers majoring in mathematics education who were undergoing teacher training at three different universities. Data were gathered through interviews, observations, and document reviews. Thematic analysis was employed to analyse the data. The study findings reveal contradictions with respect to theory and practice within the mathematics education programmes at South African universities. While the programmes contribute to the formation of active citizenry through the development of democratic skills and values, together with the incorporation of social justice issues in mathematics classrooms, they also inhibit and disempower students, given that the offerings emphasize the importance of teaching and testing, as well as the acceptance or rejection of “right” answers. Based on the findings, it is recommended that educators democratise mathematics education classrooms and adopt a humanising pedagogical approach based on care, trust and respect.